Sistem Telemetri Suhu dan Kelembaban Relatif pada Digester Anaerobik Menggunakan Telepon Seluler Cerdas Berbasis Android - admin, Novianda Fratama . (Faculty of Engineering, Universitas Tanjungpura, 2013)
The telemetry system developed in this research used a smartphone based on Android Operating Sistem (OS). Android was chosen since it has become popular with open source framework. The designed system was equipped with an SD Card for recording measurement data. The purpose of this research was to implement a telemetry system that could display the measurement data to the Android interface as table and graph in real time. This system consisted of two parts, that parts were hardware and software. Software part was an application installed on Android phone built using Eclipse IDE served to send commands to the hardware and displayed the measurement data. Hardware part was placed at the anaerobic digester and recorded the temperature and relative humidity (RH) data to SD Card and sent it to an Android smartphone if there was an order from application in smartphone. Data collected by LM35 and SHT11 sensor were compared with Digital Thermo-Hygrometer. Maximum and minimum error values of LM35 sensor were 1.46 oC and 0.02 oC respectively. Highest and smallest temperature error values of SHT11 sensor were 1.68 °C and 0.08 °C respectively, while maximum and minimum RH error values of SHT11 were 2.98 %, and 0.13 % respectively. Electrical energy consumption was 0.623 Wh with cycle time 30 minute and sampilng time 1 minute. From the test results the telemetry system could work properly for both hardware and software. Keywords– telemetry, temperature and relative humidity, anaerobic digesters, Android OS, SD Card